Social Taboos and Menstrual Practices in the Pindar Valley. (February 2019) - Joshy, Nixon; Prakash, Kamini; Ramdey, Komal
Menstruating women in remote villages of the Himalayas still practise segregation due to the belief that menstrual blood is impure. They are confined to the cowshed ( goth ) and are not allowed to interact with others. Although Bageshwar district has been declared as open defecation free and every household has a toilet, menstruating women continue to defecate in the open because they are not allowed to use sanitation facilities used by others. Menstrual taboos have an impact on the mobility, health, education and self-esteem of women and adolescent girls. This article looks at the taboos that exist in the Pindar Valley and how women and adolescent girls cope when they have their period. What is the impact of these taboos on the women and girls? How do men and women perceive these taboos? What are the key barriers to changing these practices? How have women negotiated this change given the rigid traditions that have been handed down the centuries?